Klucz do sukcesu w zarządzaniu projektami - Wąsowicz, Marek (Key to success in project management, 2006)
In this article some factors which influence the success management projects in the company were described. They are as follows: appointing the project manager, describing the goal of the project in the clear way, appointing the project team, supporting the management board of the company for the project. The main reasons of the failure of the projects were also mentioned. The authors described some ways of rising the effectiveness of the project management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 496-503